Who cares about the cargo?: Container economies in a European transshipment port. - Leivestad, Hege Høyer (Focaal, 2021)
While the shipping container has been hyped as the most potent symbol of global trade, it is simultaneously a unit of measure, a medium of exchange, and a material abstraction of heterogeneous use value. This article places the container and its anonymized cargo as part of the everyday logistics of commodity circulation in the Spanish Port of Algeciras Bay—a transshipment hub at the Strait of Gibraltar. By disentangling the shipping container's multiple repertoires, this article focuses on how the shipping container transforms and converts the value of cargo and mediates logistics labor in the port.